Associations between the type and number of chronic diseases and suicidal thoughts among Korean adults. (February 2021) - Huh, Youn; Kim, Seon Mee; Lee, Jun Hyung; Nam, Ga Eun
Highlights: The presence of renal failure, asthma, atopic dermatitis, stroke, and arthritis was associated with increased risk of suicidal thought. As the number of chronic diseases increased, the percentage and odds of suicidal thoughts tended to increase. Early detection and intervention of chronic diseases may be essential in developing suicide prevention strategies for adults with chronic diseases. Abstract: Suicide and chronic diseases are global public issues. However, the relationship between chronic diseases, multimorbidity, and suicidal thoughts is unclear. Thus, we aimed to examine the association between the type and number of chronic diseases and suicidal thoughts among Korean adults. We analyzed data from the Korea National Health and Nutrition Examination Survey. A total of 16, 059 individuals participated. We performed a multivariable logistic regression analysis adjusted for age, sex, educational level, personal income, smoking status, alcohol consumption, body mass index, comorbidity, and depressive mood, and calculated odds ratios (ORs) and 95% confidence intervals (CIs) of having suicidal thoughts. Suicidal thoughts were reported by 5.2% of participants. After adjusting for confounding variables, renal failure (OR: 4.43, 95% CI: 1.97–9.96), asthma (2.10, 1.42–3.11), atopic dermatitis (1.77, 1.15–2.70), stroke (1.59, 1.01–2.53), and arthritis (1.31, 1.02–1.69) were associated with higher risks of suicidal thoughts compared to no diagnosis. Participants with five or more chronic diseases had 2.78 times (95% CI: 1.40–5.50) higher odds of suicidal thoughts than those without chronic diseases. Having more chronic diseases was associated with a greater risk of suicidal thoughts. Early detection of and interventions for chronic diseases may be essential in developing suicide prevention strategies for adults.